2021
DOI: 10.1186/s41043-021-00235-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and behaviour on salt intake and its association with hypertension in the Malaysian population: findings from MyCoSS (Malaysian Community Salt Survey)

Abstract: Background High blood pressure or hypertension has become one of the main health problems, worldwide. A number of studies have proven that an increased intake of salt was related to an increased prevalence of cardiovascular diseases. Of late, its relationship with high salt intake has received a lot of attention. Studies in Malaysia have shown both rising hypertension over time as well as high salt consumption. Actions to reduce salt intake are essential to reduce hypertension and its disease b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
3
3
1
Order By: Relevance
“…Several food vendors were knowledgeable about the health problems that can be associated with excessive intake of cooking salt. This finding about several food vendors having good knowledge of the health consequences of excessive salt intake corroborates several other studies which found a good level of knowledge of health consequences of excessive salt intake in their study populations (Addo et al, 2006;Azubuike et al 2014;Baharudin et al, 2021). The various health problems of excessive salt intake such as hyperhidrosis, hypertension, diabetes, kidney problems, heart diseases identified by the study participants are in tandem with evidence on impacts of excessive salt intake noted in several studies (Rust and Ekmekcioglu, 2016;WHO, 2020;Hunter et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several food vendors were knowledgeable about the health problems that can be associated with excessive intake of cooking salt. This finding about several food vendors having good knowledge of the health consequences of excessive salt intake corroborates several other studies which found a good level of knowledge of health consequences of excessive salt intake in their study populations (Addo et al, 2006;Azubuike et al 2014;Baharudin et al, 2021). The various health problems of excessive salt intake such as hyperhidrosis, hypertension, diabetes, kidney problems, heart diseases identified by the study participants are in tandem with evidence on impacts of excessive salt intake noted in several studies (Rust and Ekmekcioglu, 2016;WHO, 2020;Hunter et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the finding also revealed that inadequate knowledge of health problems of excessive use of cooking salts and other condiments still existed among some food vendors. Similar pattern of result was noted in a study conducted by Baharudin et al (2021). Just like Baharudin et al (2021) noted, it is might be that some of these food vendors do not have basic exposure to information on health problems that could be associated excessive salt intake.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In comparison with prior research [ 50 , 51 ], our study indicated that behavior was the only salt-related KAP associated with dietary sodium intake among college students. Additionally, based on our findings, college students scored the highest in knowledge related to salt intake, followed by a decrease in the proportion of high scores in attitudes, and the lowest high scores in behavior.…”
Section: Discussioncontrasting
confidence: 81%
“…In the attitude domain, the item of "Salt consumption does not affect blood pressure" was shown to have a significant difference. Poor attitude in salt intake could lower the awareness regarding hypertension; hence, preventive measures through massive widespread training is necessary [29]. The significant difference in the practice domain was found in the item of "I take time to rest when I am tired or stressed".…”
Section: Discussionmentioning
confidence: 99%